Strategi Komunikasi Berbasis Nilai-Nilai Islam - Radja Aqilla Hafizh; Azzam Hilmy Tsani; Ismail Mubarok (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
In communicating, of course, we must need the right strategy to improve effectiveness and quality. In Islam we are taught how to communicate well in order to form good morals. Communication can be in the form of interaction between each other. Interaction has functions that can help humans in communicating, including conveying a message carried out by the communicant to the communicator, and how the message conveyed can be processed by the communicator and what impact it produces. This journal aims to inform the public how to implement communication strategies in accordance with Islamic values. This research uses a qualitative approach with literature study methods, and observation. The results showed that communication strategies based on Islamic values have several characteristics, including: sincerity, merit, ethics, justice and accountability, and compassion. Communication strategies based on Islamic values can increase effectiveness, credibility, and harmony in communication. This study provides recommendations for communicators, especially communicators in the fields of education, media, organizations, and society, to apply communication strategies based on Islamic values in their communication activities. This study also provides suggestions for future researchers to develop and test communication strategies based on Islamic values in a broader and varied context.